2020
DOI: 10.3352/jeehp.2020.17.3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a narrative medicine program on reflective capacity and empathy of medical students in Iran

Abstract: Purpose: Narrative medicine consists of the expression of medical experiences and the reflection on narratives to foster empathic communication with patients. Reflecting on narratives increases self-awareness and recognition of the feelings of the narrator or the story’s main character, which in turn affects the audience. This study was conducted to examine the impact of a narrative medicine program on the reflective capacity and empathy of medical students.Methods: A quasi-experimental study was performed dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 13 publications
4
32
0
7
Order By: Relevance
“…Thus, the allocation and use of a means through which trainees can develop their professional identity seem heavy tasks [10]. NM is considered to be an innovative and effective way to stimulate the professional development of medical students by educating them to approach the patient's experience of illness with more understanding, compassion, reflection and empathy [15,16]. Our previous research found that exposure to an NM program increased empathy scores among health care practitioners, as measured via the Jefferson Scale of Empathy, Health Professions Version [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the allocation and use of a means through which trainees can develop their professional identity seem heavy tasks [10]. NM is considered to be an innovative and effective way to stimulate the professional development of medical students by educating them to approach the patient's experience of illness with more understanding, compassion, reflection and empathy [15,16]. Our previous research found that exposure to an NM program increased empathy scores among health care practitioners, as measured via the Jefferson Scale of Empathy, Health Professions Version [8].…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of teaching pedagogies has been used to develop empathy, compassion and respect for patients in medical students (30)(31)(32)(33) These include, but not limited to, patients' narratives and creative arts, drama workshops, communication skills, reflective writing, video-based learning and experiential learning (34)(35)(36)(37). Lastly, the impact of role modeling and hidden curriculum in teaching compassion and empathy is well-established (38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…A 6-year longitudinal study by Kataoka et al was able to show a positive influence of communication training on empathy of medical students [ 46 ]. Daryazadeh et al used a narrative approach to train self-reflection and empathy and were able to show an increase in both after a session of only two hours [ 47 ]. Other studies with a wide variety of training approaches have also shown an improvement in the doctor/student-patient relationship [ 48 ].…”
Section: Discussionmentioning
confidence: 99%